2000
DOI: 10.1677/joe.0.1660173
|View full text |Cite
|
Sign up to set email alerts
|

Tri-iodothyronine induces proliferation in cultured bovine thyroid cells: evidence for the involvement of epidermal growth factor-associated tyrosine kinase activity

Abstract: The effects of the tri-iodothyronine (T 3 ) secreted by thyroid cells on the growth of the thyrocyte are poorly known. In this study we analyzed the effects of T 3 on the proliferation of bovine thyroid follicles in primary culture previously depleted of endogenous T 3 . Cellular deoxiribonucleic acid (DNA) synthesis, determined by [ 3 H]thymidine incorporation, was stimulated by T 3 (0·1-5·0 nM) for 24 h in a concentration-dependent fashion with a maximal effect at 1·0 nM T 3 (P<0·01). This T 3 action was tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…According to Shan et al (2009), the height of the follicular cells is an objective indicator of the thyroid gland activity. Lower proliferative activity of thyrocytes (presented in ewes by the level of PCNA) is according to Di Fulvio et al (2000) a sign of lower activity of the thyroid gland. This fact was confirmed by correlation between count of PCNA positive cells and percentage of large or small follicles and other correlations.…”
Section: Discussionmentioning
confidence: 99%
“…According to Shan et al (2009), the height of the follicular cells is an objective indicator of the thyroid gland activity. Lower proliferative activity of thyrocytes (presented in ewes by the level of PCNA) is according to Di Fulvio et al (2000) a sign of lower activity of the thyroid gland. This fact was confirmed by correlation between count of PCNA positive cells and percentage of large or small follicles and other correlations.…”
Section: Discussionmentioning
confidence: 99%
“…T 3 is considered a primary liver mitogen (Francavilla et al, 1994;Malik et al, 2003). It also accelerates wound healing of the skin (Safer et al, 2005), induces proliferation of cultured bovine thyroid cells (Di Fulvio et al, 2000), of bone marrow pro-B cells (Foster et al, 1999), of pancreatic acinar cells (Ohmura et al, 1997;Ledda-Columbano et al, 2006) of human insulinoma cells (Verga Falzacappa et al, 2006), and of renal proximal tubular epithelial cells (Ohmura et al, 1997). Finally, it increases DNA synthesis in osteoblasts (Kassem et al, 1993).…”
Section: Thyroid Hormones and Cov434 Cell Proliferationmentioning
confidence: 99%
“…Animal studies have demonstrated that T3 is a liver mitogen and promotes proliferation of hepatocytes, if given after partial hepatectomy and, its effect depends on the type and developmental state of the cell (7,8). T3 also has positive effects on wound healing and on proliferation of cells, including cultured bovine thyroid cells, bone marrow pro-B cells, pancreatic acinar cells and renal proximal tubular epithelial cells (9,10,11,12,13). There are indications that T3 is required for branching morphogenesis and epithelial/mesenchymal differentiation of the lungs (14).…”
Section: Introductionmentioning
confidence: 99%